Manufacture of different value added seaweed products and their acceptance to consumers (Asian Journal of Medical and Biological Research, 2017)
Naturally available seaweeds has not been utilized significantly in Bangladesh. In order to make a way for effective utilization of seaweeds, this study was focused on manufacture of different value added seaweed products and their acceptance to consumers. Four value added seaweed food products; namely, seaweed jelly, soup, icecream, curd; two functional food products, namely, seaweed singara, samucha/samosa, and two cosmetic products, namely, seaweed face pack, shampoo were prepared at Fish Processing Laboratory, Bangladesh Agricultural University (BAU), Mymensingh. Hypnea sp. seaweed powder was used in manufacture of all the products. For seaweed jelly, soup, ice-cream and curd consumer acceptance was 66.67%, 50%, 41.67% and 83.34%, respectively. For seaweed singara and samucha/samosa, 100% acceptance was found. Seaweed face pack and shampoo got 100% and 66.67% consumers acceptance, respectively. Thus, all these products have potential to be produced commercially.Asian J. Med. Biol. Res. December 2016, 2(4): 639-645